The Influence of Parental Involvement in Online Learning on the Emotional Regulation of Elementary School Children - Veronika, Laura; Nabila, Nabila; Rahman, Arif (Acta Psychologia, 2025)
This study explores the influence of parental involvement in online learning on the emotional regulation of elementary school-aged children, particularly in the context of increased reliance on digital education following the COVID-19 pandemic. As online learning environments shift the role of educational guidance into the home, the emotional well-being of children has become increasingly intertwined with the quality and consistency of parental support. Using a mixed-methods approach involving surveys and interviews with parents, teachers, and students across several elementary schools in Malang, Indonesia, the research finds that higher levels of parental engagement such as helping with assignments, setting routines, and providing emotional encouragement correlate strongly with improved emotional regulation in children. Specifically, children whose parents were actively involved demonstrated reduced signs of anxiety, better frustration management, and increased concentration during online lessons. The study highlights the vital role of the home environment in shaping a child’s emotional development during digital learning and calls for collaborative efforts among educators, parents, and policymakers to strengthen support systems. These findings contribute to the growing field of digital pedagogy and child development by emphasizing the importance of emotional support in academic success, particularly in remote learning settings.